Characterizing the surface forces between two individual nanowires using optical microscopy based nanomanipulation. (5th April 2018) - Xie, Hongtao; Mead, James L; Wang, Shiliang; Fatikow, Sergej; Huang, Han
Abstract: The adhesion and friction between two Al2 O3 nanowires (NWs) was characterized by the use of optical microscopy based nanomanipulation, with which peeling, shearing and sliding was performed. The elastically deformed shape of the NWs during peeling and shearing was used to calculate the adhesion and frictional forces; force sensing was not required. The obtained adhesion stress between two Al2 O3 NWs varied from 0.14 to 0.25 MPa, lower than that observed for carbon nanotube junctions, and was attributed to van der Waals attraction. Stick-slip was observed during the shearing and sliding of two NWs, and was the consequence of discrete contact between surface asperities. The obtained static and kinetic frictional stresses varied from 0.7 to 1.3 MPa and 0.4 to 0.8 MPa, respectively; significantly greater than the obtained adhesion stress.